Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan PT. Ace Hardware Indonesia Tbk. Periode 2019-2021 - Ayu Andrianie; Lince Afriyenny; Dian Ananda Febiola (BADAN PENERBIT STIEPARI PRESS, 2023)
PT. ACE Hardware Indonesia Tbk. is a retail company that operates in the field of home furnishings and lifestyle products. This company has proven to be the most resilient retailer in facing the Covid-19 pandemic. This can be seen from the decline in sales which is relatively lower compared to other retailers. This writing aims to see how the financial performance of PT. ACE Hardware Indonesia Tbk. 2019-2021 period.The type of data used in the research is quantitative data using the financial ratio analysis method. The financial ratios used are liquidity ratios (current ratio, quick ratio, cash ratio), solvency ratios (debt to asset ratio, debt to equity ratio), and profitability ratios (gross profit margin, net profit margin, return on equity, operating profit margin). The data source used in this research is secondary data. Data collection techniques use documentation studies. The documents used are secondary data which includes financial position reports and profit and loss statements from 2019-2021 which are listed on the Indonesian Stock Exchange.The results of the research show that the liquidity ratio has quite good financial performance, even though during 2019-2021 the company continues to experience fluctuations (ups and downs), the profitability ratio shows that the company's financial performance is not good in 2019 capital turnover, this can be seen in the ratio of company that is far below the trade sector average (industry average), but in 2020-2021 the profitability ratio shows very good financial performance, this proves that even in the Covid-19 Pandemic, PT. ACE Hardware Indonesia Tbk. is the most resilient retailer in facing the Covid-19 pandemic, and the solvency ratio shows good financial performance, because PT. ACE Hardware Indonesia Tbk. has a ratio that is low or below the trade sector average (industry average). This shows that the company can guarantee its debts with a number of assets owned by the company.